MEGASPORAS CRETACICAS DE LA FORMACION SPRINGHILL EN EL SUBSUELO DE ARGENTINA Y ·CHILE AUSTRAL (Ameghiniana, 2014)
In this paper sistematic descriptions of Cretaceous megaspores are presented. Specimens were obtained from drill cores in the Austral basin (or Magallanica), in Argentinian and Chile at depths of 1839 to 1959 m. Several species including Triletes gamerroi n. sp., Triletes sp., Paxillitriletes menendezii n. sp., Paxillitriletes magellanica n. sp., Minerisporites labiosus, were determined. In addition to the above mentioned megaspores, cuticle rests, seeds, sporangium and Dictyothylakos sp. (tridimentional net of probable algal origin) were identified. The specimens were studied and photographed with transmitted light and also via .Scanning Electron Microscopy. P. menendezii and T. gamerroi species were analyzed with the Transmission Electronic Microscope, detecting the microstructure and component membrane thickness.